Anthropogenic lexemes and the structure of man’s and woman’s image in modern Russian anti-proverbs with gender - O. B. Abakumova; N. V. Kiryukhina (Дискурс профессиональной коммуникации, 2019)
The aim of the paper is to analyze ways of structuring images of man and woman in modern anti-proverbs of the Russian people. The term “anti-proverb” offered by W. Mieder signifies language units of wide range: proverbs and sayings that are opposed to traditional paremias; inverted biblical sayings, aphorisms and winged words of the famous people, obscene and swear proverbs, wellerisms. Anti-proverbs show dynamics of proverbs’ existence, they are one of the new sources of their life in the language. For the research the authors selected modern Russian anti-proverbs from the dictionary by H. Walter and V. Mokienko, which possess anthropogenic lexemes, that are nouns with semantic dominant seme of sex. The paper offers classification of anti-proverbs according to sub-concepts, that reflect characteristics of men and women, which are in focus of attention of the people belonging to certain social group inside the modern Russian society. The analysis showed the gynocentric character of Russian culture in the background of masculine view of the world.